İhvân-ı Safâ'nın Nübüvvet Anlayışı - Aslan, Recep (Muş Alparslan Üniversitesi, 2019)
Ikhwân al-Safâ, who left their mark on the last periods ofAbbasid State with their effective statements, revealed their principles thateffected centuries in Rasâil Ikhwânal-Safâ, consisting of four chapters and fifty-two tracts. Ikhwân al-Safâ exhibited adifferent understanding in the interpretation of religious texts in thesetracts. Envisagement of Ikhwân for the concepts such as prophethood, angel, devil, hereafter, heaven, hell and etc. is quite different from what is knownin the Islamic thought tradition. According to Ikhwân al-Safâ, the prophets are the messengers between Allah Himselfand His creatures. Ikhwân, who describe theprophets as “doctors of the feelings”,  likens their mission to that of doctors whose treatment methods aredifferent according to the differences in diseases that occur in the bodies invarious times and places.In this article, wewill discuss the concept of prophethood of Ikhwân al-Safâ. For this reason, in this study, we will try toexamine how the issue of prophethood is discussed in Rasâil Ikhwân al-Safâ. As a method; we will try to evaluate themeanings / interpretations that they have attributed to the concept ofprophethood by scanning Ikhwân al-Safâ Tracts.

Etkili söylemleriyle Abbâsî Devleti’nin sondönemlerine damga vuran İhvân-ı Safâ, asırlara etki eden ilkelerini, dörtbölümden oluşan elli iki risâleye sığdırdıkları Resâilu İhvâni’s-Safâadlı eserde ortaya koymuşlardır. İhvân-ı Safâ, bu risalelerde dini metinlerinyorumlanmasında farklı bir anlayış sergilemiştir. İhvân’ın nübüvvet, melek, şeytan,   ahiret, cennet, cehennem vb.tasavvurları, İslam düşünce geleneğinde bilinenden oldukça farklıdır. İhvân-ıSafâ’ya göre, Peygamberler, Allah’ın kendisiyle mahlûkatı arasındakielçilerdir. Peygamberleri “gönül doktorları” olarak niteleyen İhvân, onların misyonunu, çeşitli zaman ve yerlerde bedenlere ârız olan hastalıkların farklılığına göretedavi yöntemleri de farklı olan doktorların misyonuna benzetmektedir. Bu makalede, İhvân-ı Safâ’nın nübüvvet anlayışıele alınmıştır. Bu sebeple bu çalışmada İhvân-ı Safâ Risâleler’indenübüvvet konusunun nasıl ele alındığı irdelemeye çalışılmıştır. Yöntem olarak;İhvân-ı Safâ Risâleler’ini taramak suretiyle nübüvvet kavramınayükledikleri anlamları/yorumları değerlendirilmiştir.
Prophethood Understanding of Ikhwân Al-Safâ
dinbil
Keywords: Ikhwân al-Safâ; Prophethood; Prophet; Philosophy; Tracts; İhvân-ı Safâ; Nübüvvet; Peygamber; Felsefe